Pengaruh Project Based Learning Menggunakan Peer Teaching Terhadap Hasil Belajar Siswa di SMKNegeri 8 Padang - Arif Bahy Sefitra; Delvi Asmara (Indo Publishing, 2026)
This research is motivated by the need for innovative learning strategies that can improve student engagement and learning outcomes, especially in the Network Infrastructure Administration subject. The purpose of this study is to analyze the effect of the Project Based Learning model using Peer Teaching on the learning outcomes of class XI students at SMK Negeri 8 Padang. This study uses a quantitative approach with a quasi-experimental method and a Pretest-Posttest Control Group Design design. The sample consists of two classes selected using saturated sampling techniques, namely the experimental class (XI TJKT 1) which uses the PjBL model using Peer Teaching and the control class (XI TJKT 2) which uses the Project Based Learning model. The research instrument is in the form of multiple-choice questions (pre-test and post-test) which have been tested for validity, reliability, level of difficulty, and discrimination. Data collection techniques are carried out through learning outcome tests and documentation. Data analysis involved normality, homogeneity, and independent sample t-tests using SPSS 25. The results showed a significant difference between the experimental and control classes, with average posttest scores of 83.2 and 70.2, respectively. The PjBL model using peer teaching has proven effective in significantly improving student learning outcomes while creating an interactive and collaborative learning environment. Therefore, the implementation of this model is recommended as an alternative learning strategy that can improve the quality of classroom learning.